2010
DOI: 10.1111/j.1476-5381.2010.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PDE2 and PDE5 by specific GAF ligands: delayed activation of PDE5

Abstract: By controlling intracellular cyclic nucleotide levels, phosphodiesterases (PDE) serve important functions within various signalling pathways. The PDE2 and PDE5 families are allosterically activated by their substrate cGMP via regulatory so-called GAF domains. Here, we set out to identify synthetic ligands for the GAF domains of PDE2 and PDE5. EXPERIMENTAL APPROACHUsing fluorophore-tagged, isolated GAF domains of PDE2 and PDE5, promising cGMP analogues were selected. Subsequently, the effects of these analogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 43 publications
2
28
1
1
Order By: Relevance
“…This is in stark contrast to the observations made for PDE10 (see above) and for PDE2 and PDE5 (31). Here, analogue-mediated stimulation is observed only at low concentrations of the physiological nucleotides; higher concentrations of the physiological nucleotides led to stimulation of the enzymes by themselves, thereby masking stimulation by the respective analogue.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…This is in stark contrast to the observations made for PDE10 (see above) and for PDE2 and PDE5 (31). Here, analogue-mediated stimulation is observed only at low concentrations of the physiological nucleotides; higher concentrations of the physiological nucleotides led to stimulation of the enzymes by themselves, thereby masking stimulation by the respective analogue.…”
Section: Resultscontrasting
confidence: 55%
“…and PDE11 (Ala 174 -Val 580 ) were amplified by PCR and subcloned into pcDNA3 between the open reading frames of CFP and YFP as described previously (29). HEK 293 cells were grown in 75-cm 2 flasks (30) and transfected as described (31). Two or 3 days post-transfection, cells were harvested and lysed by sonication (Branson) in 500 l of buffer (either 50 mM NaCl, 1 mM EDTA, 50 mM triethanolamine/HCl, pH 7.4 for expression of PDE holoenzymes or 25 mM triethanolamine/HCl, pH 7.4 for FRET constructs with both buffers containing 2 mM DTT and mammalian protease inhibitor cocktail (Sigma-Aldrich)).…”
Section: Phosphodiesterases (Pde)mentioning
confidence: 99%
“…Intriguingly, PDE2 is stimulated up to 40-fold by cGMP, establishing a potentially important cellular cross talk to the cardioprotective natriuretic peptide and NO systems ( Fig. 1) (Jager et al 2010). We have shown that PDE2 abundance, activity, and transcript levels are upregulated in human and animal models of HF (Mehel et al 2013).…”
mentioning
confidence: 79%
“…Assay of PDE Activity-PDE activity was measured by the conversion of [ 32 P]cyclic nucleotide monophosphate into [ 32 P]nucleotide monophosphate as described previously (21). Reaction mixtures contained 0.1 l of the striatal or HEK cell homogenates.…”
Section: Methodsmentioning
confidence: 99%